Primary antifungal prophylaxis in hematological malignancies. Updated clinical practice guidelines by the European Conference on Infections in Leukemia (ECIL) - Pagano, Livio; Maschmeyer, Georg; Lamoth, Frederic; Blennow, Ola; Xhaard, Alienor; Spadea, Manuela; Busca, Alessandro; Cordonnier, Catherine; Maertens, Johan (Leukemia, 2025)
At the 10th European Conference on Infections in Leukaemia (ECIL), the guidelines for antifungal prophylaxis in pediatric and adult patients with hematological malignancies (HM) were updated and some changes introduced. Regarding acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) patients undergoing remission induction chemotherapy, a B-II grading has been assigned to isavuconazole, micafungin, and caspofungin, based on non-randomized studies that have shown efficacy in preventing invasive fungal diseases (IFD). Regarding high-risk MDS patients treated with azacytidine, prophylaxis with posaconazole during the first four cycles of treatment is supported in the literature. Prophylaxis is not indicated in patients treated for myeloproliferative neoplasms (NPM), acute lymphoid leukemia (ALL), and Hodgkin lymphoma (HL). For patients with chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma (NHL), prophylaxis is not generally indicated. For patients with multiple myeloma (MM), prophylaxis is not indicated and the limited epidemiological data available do not support the use of prophylaxis in subjects treated with bispecific antibodies. For patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT), no substantial changes were made, apart from the addition of isavuconazole with grading B-II in the post-engraftment period. In patients undergoing auto-HSCT, antifungal prophylaxis is not indicated. Previous ECIL guidelines did not include CAR-T cells. The expert panel proposes to endorse the use of anti-mold prophylaxis in high-risk patients during pre-infusion and post-infusion, while in low-risk patients, anti-yeast prophylaxis can be recommended (B-II). For pediatric hematology patients, based on newly published data, caspofungin received a B-I grading as mold-active prophylaxis. Moreover, patients with ALL with insufficient treatment response during induction therapy, and children older than 12 y.o are now considered at high risk for IFD and are recommended to receive antifungal prophylaxis.